A novel intra-abdominal retraction device with an extra-abdominal magnetic manipulator for minimally invasive surgery - Jeon, Yong Ho; Ahn, Dahoon; Lee, Kil Yeon; Park, Sun Jin; Lee, Moon Gu (Journal of Mechanical Science and Technology, 2018)
Traction and retraction are important techniques used to increase visibility in the dissection plane during minimally invasive surgery (MIS). However, the complexity of performing these techniques during MIS requires the surgeon to have an assistant. Some devices have been devised to allow a surgeon to carry out these procedures without additional aid. However, these devices still have problems including having insufficient force, being difficult to use, and consisting of toxic materials. In this study, a remote magnetic traction and retraction device consisting of an extra-abdominal handheld magnetic manipulator and an intra-abdominal attractee made of a bullet, hook, and a wire is proposed. The attractee is made of biocompatible materials. To design a device with sufficient pulling force, magnetostatic finite element simulations were conducted. The device was verified in a series of non-survival porcine laparoscopic cholecystectomies; it was shown to eliminate the need for an assistant. The proposed device has the potential to be applied to MIS, improve health recovery for patients, and save medical costs.
Keywords: Cholecystectomy; Finite element simulations; Laparoscopic cholecystectomy; Laparoscopic surgery; Minimally invasive surgeries (MIS); Minimally invasive surgery; Natural orifice transluminal endoscopic surgeries; Retraction devices; Cholecystectomy; Laparoscopic surgery; Natural orifice transluminal endoscopic surgery (NOTES); Traction and retraction device